AYAT-AYAT RIBA DALAM AL-QUR’AN: PENDEKATAN HISTORIS - Ruslan, Ruslan (At-Taradhi Jurnal Studi Ekonomi, 2016)
Abstract: The verses on usury(riba) appeared in two periods; Makiyah and Madaniyah. Scholars disagree about the revelations of usury. Some people think that is the refection of the usury laws while others looked at the verses stand alone. When people understood them independently of all the words usury in the Qur'an connotes illegal except al-Rum (30): 39 there is a commentator who argue that the word usury in this verse is not prohibited usury because it means gifts so that there are two kinds of usury: illegal and legal usury. The writer tends to say in this verse that there is already nash signal (siy?qul kalam) that led to the prohibition of usury. Its law Illat of usury practice can be destructive to the economy of the people / society, market imbalances and injustices. Therefore, the author also suggests hindering usury with all its forms and be careful of conventional banks and modern fnancial that wants to help the economy of the people. Although now banks and fnancial are very modern.Abstrak: Ayat-ayat tentang riba turun di dua periode; Makiyah dan Madaniyah. Ulama berbeda pendapat tentang ayat-ayat riba. Ada yang beranggapan mencerminkan tahapan hukum riba dan sementara yang lain memandangnya ayat-ayatnya berdiri sendiri. Bila dipahami secara mandiri semua kata riba yang ditunjuk Alquran berkonotasi haram kecuali al-R?m (30): 39 ada mufassir yang berpendapat riba dalam ayat ini bukan riba yang dilarang karena berarti hadiah (pemberian) sehingga ada dua riba: riba haram dan riba halal. Penulis cenderung mengatakan dalam ayat ini sudah ada isyarat nash (siy?qul kalam) yang mengarah kepada dilarangnya riba. Illat hukumnya praktik riba dapat merusak tatanan ekonomi umat/masyarakat, ketidak-seimbangan pasar, dan ketidakadilan. Oleh karena itu penulis juga menyarankan jauhilah riba dengan segala bentuknya dan berhati-hati terhadap bank-bank konvensional dan fnansial-fnansial modern yang berdalih membantu perekonomian umat. Walaupun bank-bank dan fnansial-fnansial yang ada sekarang sudah sangat modern.